PELATIHAN PENGAJARAN BAHASA INDONESIA DAN PENGEMBANGAN BAHAN AJAR DI ERA DIGITAL PADA GURU SMP SE-KECAMATAN DIWEK - Thahirrah, Nadia Nur; Supratno, Haris Supratno; Raharjo, Resdianto; Kholifatu A.S, Arisni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This Community Service Program (PKM) was carried out by the PKM Team of Surabaya State University (UNESA) in collaboration with Hasyim Asy'ari University (UNHASY) Tebuireng Jombang and the Indonesian Language Teacher Working Group (MGMP) of Jombang Regency. The program aims to improve the competence of Indonesian Language and Literature teachers in public and private junior high schools throughout Jombang Regency in facing the challenges of learning in the digital era. The training focused on five main aspects, namely: (1) mastery of Indonesian spelling, (2) skills in writing standard sentences based on digital technology, (3) application of innovative Indonesian language learning, (4) innovation in Indonesian literature learning, and (5) development of creative teaching materials. The implementation methods included lectures, discussions, question and answer sessions, assignments, practice, mentoring, and direct supervision at partner schools. The program was attended by 232 teachers, far exceeding the initial target of 50 participants, demonstrating the high level of enthusiasm and need for competency improvement among teachers. The results achieved include an increase in participants' understanding and skills in technology-based teaching, the development of innovative teaching materials, and the publication of scientific articles, online media articles, and video documentation of activities. This program has succeeded in creating a more interactive and digital-friendly learning ecosystem, which is expected to improve the quality of Indonesian language and literature teaching in Jombang Regency towards the achievement of a literate and character-building generation.